Corrigendum: Oligodendrocyte precursor cell-derived exosomes combined with cell therapy promote clinical recovery by immunomodulation and gliosis attenuation (Frontiers in Cellular Neuroscience, (2024), 18, (1413843), 10.3389/fncel.2024.1413843) - Santos, Sarah Ingrid Pinto; Ortiz-Peñuela, Santiago José; de Paula Filho, Alessandro; Tomiyama, Ana Laura Midori Rossi; Coser, Lilian de Oliveira; da Silveira, Juliano Coelho; Martins, Daniele dos Santos; Ciena, Adriano Polican [UNESP]; de Oliveira, Alexandre Leite Rodrigues; Ambrósio, Carlos Eduardo (Frontiers, 2024)
In the published article, there was an error in the Funding statement. In the Funding statement for the São Paulo Research Foundation, only grant 2021/09869–6 was displayed. The correct statement is São Paulo Research Foundation grant 2021/09869–6 and grant 2022/10604-0. The correct Funding statement appears below.
Keywords: extracellular vesicles; immunomodulation; multiple sclerosis; neural stem cell; neurodegeneration; oligodendrocyte precursor cell